2021
DOI: 10.3389/fonc.2021.707017
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA Sequencing Identifies PIWI-Interacting RNAs Deregulated in Glioblastoma—piR-9491 and piR-12488 Reduce Tumor Cell Colonies In Vitro

Abstract: Glioblastoma (GBM) is the most frequently occurring primary malignant brain tumor of astrocytic origin. To change poor prognosis, it is necessary to deeply understand the molecular mechanisms of gliomagenesis and identify new potential biomarkers and therapeutic targets. PIWI-interacting RNAs (piRNAs) help in maintaining genome stability, and their deregulation has already been observed in many tumors. Recent studies suggest that these molecules could also play an important role in the glioma biology. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Out of the 20 studies analyzed, four focused primarily on RCC [ 26 , 44 , 50 , 55 ], four on CRC [ 13 , 24 , 27 , 53 ], three on Head and neck squamous carcinoma (HNSCC) [ 48 , 49 , 54 ], two on Gastric cancer (GC) [ 46 , 47 ], one on Breast cancer (BC) [ 51 ], one on Diffuse large B cell lymphoma (DLBCL) [ 41 ], one on Ovarian cancer (OC) [ 42 ], one on Multiple myeloma (MM) [ 43 ], one on Glioblastoma (GBM) [ 45 ], one on NSCLC [ 25 ], and one on Hodgkin lymphoma (HL) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 20 studies analyzed, four focused primarily on RCC [ 26 , 44 , 50 , 55 ], four on CRC [ 13 , 24 , 27 , 53 ], three on Head and neck squamous carcinoma (HNSCC) [ 48 , 49 , 54 ], two on Gastric cancer (GC) [ 46 , 47 ], one on Breast cancer (BC) [ 51 ], one on Diffuse large B cell lymphoma (DLBCL) [ 41 ], one on Ovarian cancer (OC) [ 42 ], one on Multiple myeloma (MM) [ 43 ], one on Glioblastoma (GBM) [ 45 ], one on NSCLC [ 25 ], and one on Hodgkin lymphoma (HL) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of these 20 studies, nine records utilized high-throughput assays of RNA sequencing [ 13 , 45 , 47 49 , 51 , 53 55 ], seven used qRT-PCR [ 24 26 , 43 , 46 , 50 , 52 ], three used Microarray analysis [ 27 , 41 , 44 ], and one used ISH [ 42 ] for quantification of piRNAs in patients biological specimen. The majority of these studies were conducted in China (nine studies) [ 13 , 24 , 25 , 27 , 41 43 , 46 , 55 ], three studies followed by the USA [ 48 , 49 , 53 ], three in Canada [ 47 , 51 , 54 ], two in Czech Republic [ 26 , 45 ], two in Germany [ 44 , 50 ], and one in Spain [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that piRNA-36712 was low expressed in breast cancer than in matched controls and its overexpression restrains progression and chemoresistance of CC cells by interacting with SEPW1P RNAs 21 . By piRNA expression profile analysis, Bartos et al report that piRNA-9491 and piRNA-12488 were significantly dysregulated in glioblastoma cells and could reduce the ability to form colonies in vitro 17 . Here, we showed that piRNA-17458 was significantly overexpressed in CC tissues and cells when compared with that in matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recently several piRNA (e.g., piR‐9491 and piR‐2488) have also been identified to be associated with GBM disease development. [ 256 ] Regardless, up to date, no specific gene therapy targeting piRNA for CNS diseases has been demonstrated. Most of the works still focus on discovering the piRNA as the current stage.…”
Section: Gene Therapy For Cns Diseasesmentioning
confidence: 99%